Pelatihan Pengolahan Pakan Asal Limbah Pertanian di Desa Moyo Mekar Moyo Hilir Sumbawa - Muhamad Amin; SD Hasan; Oscar Yanuarianto; Suhubdy Suhubdy; Syamsul Hidayat Dilaga (Jurnal Gema Ngabdi, 2021)
As an effort to improve the knowledge and skills of rural breeders, community service activities have been carried out with the topic "Training on Feed Processing from Agricultural Waste in Moyo Mekar Village of Moyo Hilir Sumbawa." This service activity was held on the grounds that breeders in Moyo Mekar Village often experience difficulties to meet the needs of their livestock for forage, especially during the dry season, so this sometimes has an unwanted negative impact, such as the occurrence of cases of death and disease in livestock as a result of the declining condition of the livestock. This is due to the ignorance of the breeders in their efforts to overcome the shortage of forage during the dry season. This community service activity has been carried out using three methods, namely lecture, written and demonstration methods. With the lecture method, it was conveyed about the understanding and explanation of how to preserve and treat agricultural waste. Through the written method, it is conveyed by giving brochures to the breeder members. Meanwhile, with the demonstration method, the breeders directly practice ways of preserving and treating agricultural waste. Based on the results of monitoring during the activity, the results of questions and answers and the enthusiasm of the participants, it was seen that the new breeders realized how important the role of nutrition was for livestock, the availability of applying preservation and feed processing technology, and it could also be seen that they had no difficulty in adopting the material provided, then Overall this activity can be said to be quite successful. Recognizing the limitations of the breeders in terms of preservation and processing of feed which is an alternative for providing feed in the dry season, it is suggested that this kind of activity should be continued so that the expected livestock production can be achieved.